Tolerance to Effects of High-Dose Oral Δ9-Tetrahydrocannabinol and Plasma Cannabinoid Concentrations in Male Daily Cannabis Smokers - Gorelick, David A. (Oxford University Press, 2013)
Oral cannabinoids are taken for medicinal or recreational purposes, yet little is known about tolerance to their effects after high-dose extended exposure. The development of tolerance to effects of around-the-clock oral synthetic Δ9-tetrahydrocannabinol (THC) (20 mg every 3.5–6 h) was evaluated in 13 healthy male daily cannabis smokers residing on a secure research unit: 40 mg on Day 1; 100 mg on Days 2–4; 120 mg on Days 5–6. Systolic and diastolic blood pressure (BP), heart rate, and symptoms of subjective intoxication (100 mm visual-analogue scales, VAS) were assessed the morning of Day 1 (before any oral THC), and on Days 2, 4 and 6, every 30 min for 3 h after the first morning THC dose. Morning subjective intoxication ratings increased from Days 1 to 2, and then declined on Days 4 and 6. The morning THC dose increased intoxication ratings on Day 2, but had less effect on Days 4 and 6, a pattern consistent with tolerance. THC lowered BP and increased heart rate over the six days. Plasma THC and 11-OH-THC concentrations increased significantly over the first five days of dosing. Six days of around-the-clock, oral THC produced tolerance to subjective intoxication, but not to cardiovascular effects.